2018
DOI: 10.1186/s13047-018-0303-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis in foot and ankle surgery: a systematic review of the literature

Abstract: BackgroundWith the advent of bacterial resistance, it is important now more than ever to evaluate use of antibiotic chemoprophylaxis in foot and ankle surgery. Within this area of the body there may be less dissection, surgery time with smaller incisions and importantly smaller sizes of implanted fixation as compared to other bone and joint procedures. Our objective was to systematically evaluate the quality of evidence behind existing guidelines.MethodologyA systematic literature search was performed: MEDLINE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
(147 reference statements)
1
16
0
Order By: Relevance
“…A Cochrane review revealed that the use of antibiotics has not been shown to result in a difference in infection rates [22]. Using a similar dataset, a prospective cohort study by Butterworth et al [11] showed that the use of perioperative antibiotics in foot and ankle surgery may reduce the risk of infection. However, Butterworth et al [11] did not separate their study population into specific procedure groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Cochrane review revealed that the use of antibiotics has not been shown to result in a difference in infection rates [22]. Using a similar dataset, a prospective cohort study by Butterworth et al [11] showed that the use of perioperative antibiotics in foot and ankle surgery may reduce the risk of infection. However, Butterworth et al [11] did not separate their study population into specific procedure groups.…”
Section: Discussionmentioning
confidence: 99%
“…Using a similar dataset, a prospective cohort study by Butterworth et al [11] showed that the use of perioperative antibiotics in foot and ankle surgery may reduce the risk of infection. However, Butterworth et al [11] did not separate their study population into specific procedure groups. Consequently, whether antibiotic prophylaxis reduces infection rates following ingrowing toenail surgery may be unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reported as pathogens of SSIs in foot and ankle surgery are S. aureus, Pseudomonas , and Staphylococcus epidermidis , all associated with the formation of a biofilm on foreign material. 13,15,21 Since cephalosporins are effective in preventing Staphylococcus infections, cefazolin is the most often used prophylactic antibiotic in a variety of surgical procedures and is recommended for implant surgery by multiple guidelines. 4,7 The most common pathogens causing SSI in this study were S. aureus and Enterobacter cloacae .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of surgical site infections (SSIs) following orthopedic trauma surgery of foot and ankle has been reported as ranging from 0 to 9.4% [1]. In complex foot injuries, this percentage can even increase up to 25% [2].…”
Section: Introductionmentioning
confidence: 99%